Ultrasound-Guided Transverse Thoracic Muscle Plane Block (TTMPB) for Post-Sternotomy Pain: A Randomized Controlled Trial - Gill, Navkiran Singh; Mokhtar, Ariffin Marzuki; Abidin, Huda Zainal; Eu, Chong Soon; Zahari, Yusrina; Hassan, Mohamad Hasyizan (Malaysian Journal of Medical Sciences, 2025)
Background: Poorly controlled acute surgical pain after cardiac surgery results from extensive tissues injuries and associated with high pain intensity and leading to chronic pain and excessive opiod use. The aim is to analyse the pain scores, Patient Controlled Analgesia (PCA) Fentanyl requirement and spirometry values in Transverse Thoracic Muscle Plane Block (TTMPB) versus conventional opioid strategy in patients that underwent cardiac sternotomy surgeries. Methods: This is a randomized controlled trial with a total of 40 adult patients who underwent elective cardiac surgery with sternotomy to receive either intervention with TTMPB (B, n = 20) or control (A, n = 20). We measured the mean pain scores at rest and on movement post extubation using the Visual Analogue Scale (VAS), mean PCA fentanyl consumption as well as incentive spirometry volume at 0,3,6, 12, 18, 24 and 48 hours post extubation. Analysis was done using the repeated measure ANOVA. Results: At rest, there was significant reduction in pain score across different timepoints observed between both groups (F [6, 228] = 3.180, P < 0.05). On movement, a significant interaction between the TTMPB treatment and pain score at movement across different timepoints (F [6, 228] = 2.249, P < 0.001] was shown. There was also significant reduction in PCAF consumption across different timepoints (F[6, 228] = 2.080, P < 0.05). Similar outcomes were also observed in the changes of spirometry volume across different timepoints between the two study groups (F [6, 228] = 10.855, P < 0.001. Conclusion: The administration of the TTMPB resulted in significantly reduced pain scores at rest and movement, reduced the mean PCA fentanyl consumption and showed better incentive spirometry volume post extubation compared to the control group. This study supports TTMPB as efficient post operative analgesia for post cardiac surgery.